Current situation and future direction of traditional foods: A perspective review - Dwi Larasatie Nur Fibri; Siham Ayouaz; Rohmah Fitri Utami; Dimas Rahadian Aji Muhammad (jurnal1, 2022)
Innovation of traditional foods become a new paradigm in the food industry as an effort to prolong the shelf life of the food following the changes in the society’s life style. The innovation was also supported by the current advance study on packaging technology, microbiology, biotechnology, metabolomics, medicinal properties and health as well as computational methods. This review covers various definition of traditional foods and some terms closely related to traditional foods, including ethnicity and ethnoecology, the progress of innovation of traditional foods as well as the risk of the traditional food innovation in terms of product identity, culture and continuity. Geographical Indications (GI) as a strategy of protection and standardization of traditional food are, therefore, discussed in this review. At the end, a recommendation for the direction of traditional food in the future is given in order to create a paradigm on the future action for protecting traditional foods.